2021
DOI: 10.1039/d0ra08541c
|View full text |Cite
|
Sign up to set email alerts
|

Continuous selective deoxygenation of palm oil for renewable diesel production over Ni catalysts supported on Al2O3and La2O3–Al2O3

Abstract: Highly selective and stable Ni supported on La2O3–Al2O3 catalyst on the deCO/deCO2 reaction paths for the production of renewable diesel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 88 publications
(134 reference statements)
1
15
0
Order By: Relevance
“…The authors related this fast deactivation to the adsorption of the unsaturated triglycerides on the surface of the catalyst (coke formation) or due to the sintering of the Ni species on the γ-alumina surface. Similar conclusions were also drawn by Papageridis et al [36].…”
Section: Resultssupporting
confidence: 91%
“…The authors related this fast deactivation to the adsorption of the unsaturated triglycerides on the surface of the catalyst (coke formation) or due to the sintering of the Ni species on the γ-alumina surface. Similar conclusions were also drawn by Papageridis et al [36].…”
Section: Resultssupporting
confidence: 91%
“…Nevertheless, the bentonite-ZrN catalyst revealed an only 3.73% decrease in the catalyst activity towards conversion at four consecutive cycles relative to the fresh catalyst, whereas only 2.34% decreased in the catalyst activity by bentonite-ZrP. Papageridis et al 88 reported that the nitride-based catalyst had more stability than the sulfide catalyst towards the conversion of guaiacol through the hydrodeoxygenation reaction after 4 h on stream during continuous operation, whereas de Souza et al 35 showed that the phosphide-based catalyst had an insignificant deactivation towards phenol conversion through the hydrodeoxygenation reaction during 20 h on stream. According to the reusability study (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2CO → C + CO 2 (10) Carbon deposits are also produced from methane decomposition (Equation ( 11)), carbon monoxide and dioxide decomposition (Equations ( 12) and ( 13)), and ethene polymerization (Equation ( 14)) [12].…”
Section: Mechanism Of Bio-oil Steam Reformingmentioning
confidence: 99%
“…Lignocellulosic biomass, such as agricultural residues and dedicated energy crops, has a vast unused potential for continuous energy supply at a low price and with neutral carbon dioxide (CO 2 ) environmental impact [8][9][10]. The utilization of lignocelluloses can open a renewable carbon-neutral roadmap [11,12] for the production of heat, electrical power and biofuels.…”
Section: Introductionmentioning
confidence: 99%